Absence of terminal deoxynucleotidyl transferase expression in T‐ALL/LBL accumulates chromosomal abnormalities to induce drug resistance. Issue 11 (22nd February 2023) - Xiao, Hui; Wang, Siqi; Tang, Yuejia; Li, Shanshan; Jiang, Yufeng; Yang, Yi; Zhang, Yinwen; Han, Yali; Wu, Xiaoyu; Zheng, Liang; Li, Yanxin; Gao, Yijin
Abstract: T‐acute lymphoblastic leukemia/lymphoma (T‐ALL/LBL) is a malignant neoplasm of immature lymphoblasts. Terminal deoxynucleotidyl transferase (TDT) is a template‐independent DNA polymerase that plays an essential role in generating diversity for immunoglobulin genes. T‐ALL/LBL patients with TDT − have a worse prognosis. However, how TDT − promotes the disease progression of T‐ALL/LBL remains unknown. Here we analyzed the prognosis of T‐ALL/LBL patients in Shanghai Children's Medical Center (SCMC) and confirmed that TDT − patients had a higher rate of recurrence and remission failure and worse outcomes. Cellular experiments demonstrated that TDT was involved in DNA damage repair. TDT knockout delayed DNA repair, arrested the cell cycle and decreased apoptosis to induce the accumulation of chromosomal abnormalities and tolerance to abnormal karyotypes. Our study demonstrated that the poor outcomes in TDT − T‐ALL/LBL might be due to the drug resistance (VP16 and MTX) induced by chromosomal abnormalities. Our findings revealed novel functions and mechanisms of TDT in T‐ALL/LBL and supported that hematopoietic stem cell transplantation (HSCT) might be a better choice for these patients. Abstract : What's new? Terminal deoxynucleotidyl transferase (TDT) serves a critical role in promoting immune diversity. In some T‐acute lymphoblastic leukemia/lymphoma (T‐ALL/LBL) patients, however, TDT expression is lacking. Here, the authors explored the significance of TDT loss by analyzing prognosis in TDT − T‐ALL/LBL patients and via cell experiments. Patients lacking TDT had poor therapeutic responses, with increased rates of recurrence and remission failure and worse outcomes. TDT knockout in cells was associated with delayed DNA repair and decreased apoptosis, leading to an accumulation of chromosomal abnormalities that potentially facilitate drug resistance. The findings provide novel insight into TDT mechanisms in T‐ALL/LBL.